Investigation on the Performance of Innovative Powdered Activated Carbon Hybird Microbial Fuel Cell in Treating Palm Oil Mill Effluent - Lim, Ping Feng (2016)
Performance of nine 0.5L MFCs with and without PAC and cultivated at different SRTs with different feed concentrations were studied and compared for their effects on wastewater treatment, biogas and power productions. The best MFC could remove the COD from the POME up to 64.4%. This study also shows that biogas could be better produced by the MFCs which were fed with relatively higher feed concentration compared to the MFCs fed with relatively lower feed concentration. However, it was found that the power production for the MFCs fed with relatively lower feed concentration had better power density production compared to the MFCs fed with the relatively higher feed concentration. In addition, all the MFC cultivated at longer SRTs with PAC could perform better in terms of biogas production, COD removal and power production.